Acute Toxicity Nanoemultion of Ethanol Extract of Clove Leaves (Syzygium aromaticum L.) - Muthmainah Tuldjanah; Putri Natalia Laurenza Ladjeba; Rezky Yanuarty; Ayu Wuladari; Joni Tandi; Muaadzatul Izzah Sudarman (Postgraduate, University of Mataram, 2026)
Clove leaves have been widely used as traditional medicine. Clove leaves are rich in saponins, flavonoids, tannins, sterols, and essential oils. To improve the function of clove leaves, one of them is by reducing the sample size into nanoemulsion form. Nanoemulsions were prepared using the sonication method and exhibited an average droplet size of 13.3 nm. The purpose of this study was to determine the toxic properties, the dose that can cause toxic effects, and the LD50 value of nanoemulsion administration of ethanol extract of clove leaves. This study used 25 male white rats which were divided into five groups, namely a control group (nanoemulsion base) and four treatment groups receiving oral doses of 5, 50, 300, and 2000 mg/kg BW. The LD50 value was calculated using AOT425 StatPgm in accordance with OECD TG 425 (Up and Down Procedure). Mortality summary: control 0/5; 5 mg/kg BW 0/5; 50 mg/kg BW 0/5; 300 mg/kg BW 0/5; 2000 mg/kg BW 5/5. The results showed an LD50 of 798.5 mg/kg BW and, based on the GHS, it falls under Acute Toxicity (Oral) Category 4 (300–2000 mg/kg BW). Clinical signs such as piloerection, grooming, and weakness appeared mainly in the early observation phase (from 30 minutes to 4/8/12 hours) in each dose group and were reversible.